Penerapan Asas Hukum Dalam Pembuatan Peraturan Perundang- Undangan yang Berkeadilan dan Partisipatif - Siagian, Ade Onny; Utama, Andrew Shandy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This research discusses the principles of law that must be implemented in the formation of laws and regulations, and the application of legal principles in making laws and regulations that are just and participatory. With the normative juridical approach, it can be concluded that legislators often ignore legal principles, because the principle is only an abstract and general idea and does not contain sanctions. The implementation of the principles for the formation of statutory regulations and the material principles for the content of statutory regulations is not optimal, so there is still a lot of resistance or resistance from the community when it is implemented that gets resistance or resistance from the community.